2005
DOI: 10.1523/jneurosci.1674-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Programmed and Induced Phenotype of the Hippocampal Granule Cells

Abstract: Certain neurons choose the neurotransmitter they use in an activity-dependent manner, and trophic factors are involved in this phenotypic differentiation during development. Developing hippocampal granule cells (GCs) constitutively express the markers of the glutamatergic and GABAergic phenotypes, but when development is completed, the GABAergic phenotype shuts off. With electrophysiological, single-cell reverse transcription-PCR and immunohistological techniques, we show here that short-term (24 h) cultures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 51 publications
2
59
0
1
Order By: Relevance
“…Similarly, in cerebellar mossy fiber terminals, VGAT was colocalized with VGLUT1 and VGLUT2, though here all mossy fiber terminals expressed the vesicular GABA transporter. In addition to singlecell PCR data demonstrating the presence of VGAT mRNA in hippocampal granule cells (Gó mez-Lira et al, 2005; this investigation), we show here the coexistence of VGAT and VGLUT in mossy fiber terminals at the electron microscopic level using a range of VGLUT and VGAT antibodies. Comparable to the auditory system (Gillespie et al, 2005), GABA and glutamate may be released simultaneously from developing hippocampal mossy fiber terminals (Walker et al, 2001;Gutiérrez et al, 2003;Kasyanov et al, 2004;Safiulina et al, 2006).…”
Section: Vgat In Glutamatergic Neuronssupporting
confidence: 72%
See 2 more Smart Citations
“…Similarly, in cerebellar mossy fiber terminals, VGAT was colocalized with VGLUT1 and VGLUT2, though here all mossy fiber terminals expressed the vesicular GABA transporter. In addition to singlecell PCR data demonstrating the presence of VGAT mRNA in hippocampal granule cells (Gó mez-Lira et al, 2005; this investigation), we show here the coexistence of VGAT and VGLUT in mossy fiber terminals at the electron microscopic level using a range of VGLUT and VGAT antibodies. Comparable to the auditory system (Gillespie et al, 2005), GABA and glutamate may be released simultaneously from developing hippocampal mossy fiber terminals (Walker et al, 2001;Gutiérrez et al, 2003;Kasyanov et al, 2004;Safiulina et al, 2006).…”
Section: Vgat In Glutamatergic Neuronssupporting
confidence: 72%
“…For instance, an increasing body of evidence suggests that both VGLUT1 and VGLUT2 colocalize in synapses of a select subset of neurons. VGLUT1 and VGAT (Kao et al, 2004;Gó mez-Lira et al, 2005), and VGLUT2 and VGAT (Ottem et al, 2004), were found to colocalize by immunofluorescence microscopy. In addition, both VGLUT2 and VGAT were detected in a subset of presynaptic terminals in the rat hippocampus using postembedding immunogold electron microscopy (Boulland et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, different treatments, such as sustained synaptic activity or direct activation of glutamate receptors or BDNF administration, can rescue the developmental phenotype. This form of plasticity is not limited to the developmental critical period (5). These findings demonstrate an activity-dependent regulation of the matching of transmitters and their receptors in defining the identity of recently formed synapses.…”
mentioning
confidence: 71%
“…Nevertheless, it is well known that a neuron can store and presumably release the different sets of transmitters from individual axon endings [25]. The neurotransmitter choice of the neurons depends on programmed and environmental factors, and this process is neither limited by a critical period nor restricted by their insertion in a network [26]. Calcium transient patterns plays a key role in the differentiation of neural precursor cells, and their frequency may specify neuronal morphology and acquisition of neurotransmitter phenotype [27].…”
Section: B Synaptogenesismentioning
confidence: 99%